Trajectories of disability throughout early life and labor force status as a young adult: Results from the Longitudinal Study of Australian Children - Marissa Shields; Matthew J Spittal; Stefanie Dimov; Anne Kavanagh; Tania L King (Nordic Association of Occupational Safety and Health (NOROSH), 2022)
OBJECTIVES: Young people with disabilities have poorer labor force outcomes than their peers without disabilities. These understandings, however, are largely based on research assessing disability at one time point only, an approach that potentially obscures variation in disability over time. We aimed to identify trajectories of disability during childhood/adolescence and assess associations between trajectory membership and labor force status in young adulthood. METHODS: We conducted group-based trajectory modeling of disability status information from six waves [waves 2-7 (age 4/5 to 16/17 years)] of the Longitudinal Study of Australian Children. The trajectories were used to predict labor force participation (employed, unemployed, not in the labor force) at wave 8 (18/19 years), adjusted for confounders. RESULTS: We identified four trajectory groups of the prevalence of disability: low (75.5% of cohort), low increasing (9.7%), high decreasing (10.9%), and consistently high (3.9%). Individuals in the low increasing trajectory were nearly three times as likely to be unemployed at age 18/19 years compared to individuals in the low trajectory [risk ratio (RR) 2.96, 95% confidence interval (CI) 1.94-4.53]. Individuals in the consistently high trajectory had a greater RR of not being in the labor force at age 18/19 years compared to individuals in the low group (reference) (RR 3.65, 95% CI 2.21-6.02). CONCLUSIONS: Results suggest that prolonged and increasing experiences of disability among young Australians may be differentially associated with future labor force outcomes. Additional support to prepare young people for the labor force should focus on individuals who consistently or increasingly report a disability.